Analysis of Students' Creative Thinking in Proposing SPLDV Problems Viewed from Cognitive Abilities - Trisanti, Yuliana; Saleh, Hairus (INTERAKSI : Jurnal Kependidikan, 2022)
This research aims to describe the analysis of students' creative thinking in posing SPLDV problems in terms of students with high abilities and low abilities. This research is a qualitative descriptive study. The material used is Systems of Linear Equations in Two Variables (SPLDV). SPLDV are two linear equations that have solutions in the form of ordered pairs which can be represented by x, y. The results of the research are that students with high abilities in asking SPLDV problems can be included in the good category. Students with medium low ability in asking SPLDV problems are still in the sufficient category. Low ability students HY are only able to meet the indicators of creative thinking fluency. In planning and implementing SPLDV problem submissions, it is seen from cognitive ability, namely high ability and low ability are still categorized as lacking.